Aerodynamic and Inertial Loading Effects of Insect-Inspired Appendages in Small Unmanned Aerial Vehicles - Titilayo Ogunwa; Javaan Chahl (Biomimetics)
Insects enhance aerodynamic flight control using the dynamic movement of their appendages, aiding in balance, stability, and manoeuvrability. Although biologists have observed these behaviours, the phenomena have not been expressed in a unified mathematical flight dynamics framework. For instance, relevant existing models tend to disregard either the aerodynamic or the inertial effects of the appendages of insects, such as the abdomen, based on the assumption that appendage dynamic effects dominate in comparison to aerodynamic effects, or that appendages are stationary. However, appendages in insects exist in various shapes and sizes, which affect the level of both the inertial and aerodynamic contributions to the overall system. Here, the effects of the individual dynamic, inertial and aerodynamic contributions of biologically inspired appendages in fixed wing forward flight demonstrate the utility of the framework on an example system. The analysis demonstrates the effect of these aerodynamic appendages on the steady flight and manoeuvre performance of a small aircraft with an actuated aft appendage capable of movement in the longitudinal and lateral axes, analogous to an insect abdomen. We use the method to consider designs with different appendage areas. The example case showed that ignoring the aerodynamic contribution might yield useful insights depending on the size of the appendage, but including the aerodynamic effects as part of a consistent mathematical framework leads to a more comprehensive understanding of the role of appendage morphology. The method allows improved modelling for modern multivariate control system design using bioinspired appendages. Inertia-dominated appendages provided more advantages in energy-based longitudinal manoeuvres and in trimmed flight, with reduced advantage in initiating lateral manoeuvres.